Acute impact of inhaled short acting B2-agonists on 5 km running performance - Dickinson, J.; Hu, J.; Chester, N.; Loosemore, M.; Whyte, G. (Journal of Sports Science & Medicine, 2014)
Whilst there appears to be no ergogenic effect from inhaled salbutamol no study has investigated the impact of the acute inhalation of 1600 ìg, the World Anti-Doping Agency (WADA) daily upper limit, on endurance running performance. To investigate the ergogenic effect of an acute inhalation of short acting Beta2-agonists at doses up to 1600 ug on 5 km time trial performance and resultant urine concentration. Seven male nonasthmatic runners (mean ± SD; age 22.4 ± 4.3 years; height 1.80 ± 0.07 m; body mass 76.6 ± 8.6 kg) provided written informed consent. Participants completed six 5 km time-trials on separate days (three at 18 oC and three at 30 oC). Fifteen minutes prior to the initiation of each 5 km time-trial participants inhaled: placebo (PLA), 800 ìg salbutamol (SAL800) or 1600 ìg salbutamol (SAL1600). During each 5 km time-trial HR, VO2, VCO2, VE, RPE and blood lactate were measured. Urine samples (90 ml) were collected between 30-180 minutes post 5 km time-trial and analysed for salbutamol concentration. There was no significant difference in total 5 km time between treatments (PLA 1714.7 ± 186.2 s; SAL800 1683.3 ± 179.7 s; SAL1600 1683.6 ± 190.7 s). Post 5 km time-trial salbutamol urine concentration between SAL800 (122.96 ± 69.22 ug·ml-1) and SAL1600 (574.06 ± 448.17 ug·ml-1) were not significantly different. There was no improvement in 5 km time-trial performance following the inhalation of up to 1600 ìg of salbutamol in non-asthmatic athletes. This would suggest that the current WADA guidelines, which allow athletes to inhale up to 1600 ìg per day, is sufficient to avoid pharmaceutical induced performance enhancement.